Thymomectomy plus total thymectomy versus simple thymomectomy for early-stage thymoma without myasthenia gravis: a European Society of Thoracic Surgeons Thymic Working Group Study. (23rd May 2021) - Guerrera, Francesco; Falcoz, Pierre Emmanuel; Moser, Bernhard; van Raemdonck, Dirk; Bille', Andrea; Toker, Alper; Spaggiari, Lorenzo; Ampollini, Luca; Filippini, Claudia; Thomas, Pascal Alexandre; Verdonck, Bram; Mendogni, Paolo; et al.
Abstract:  : OBJECTIVES: Resection of thymic tumours including the removal of both the tumour and the thymus gland (thymothymectomy; TT) is the procedure of choice and is recommended in most relevant articles in the literature. Nevertheless, in recent years, some authors have suggested that resection of the tumour (simple thymomectomy; ST) may suffice from an oncological standpoint in patients with early-stage thymoma who do not have myasthenia gravis (MG) (non-MG). The goal of our study was to compare the short- and long-term outcomes of ST versus TT in non-MG early-stage thymomas using the European Society of Thoracic Surgeons thymic database. METHODS: A total of 498 non-MG patients with pathological stage I thymoma were included in the study. TT was performed in 466 (93.6%) of 498 patients who had surgery with curative intent; ST was done in 32 (6.4%). The completeness of resection, the rate of complications, the 30-day mortality, the overall recurrence and the freedom from recurrence were compared. We performed crude and propensity score-adjusted comparisons by surgical approach (ST vs TT). RESULTS: TT showed the same rate of postoperative complications, 30-day mortality and postoperative length of stay as ST. The 5-year overall survival rate was 89% in the TT group and 55% in the ST group. The 5-year freedom from recurrence was 96% in the TT group and 79% in the ST group. CONCLUSION: Patients with early-stage thymoma without MG who have a TT show significantly better freedom from recurrence than those who have an ST, without an increase in postoperative morbidity rate.